GENDER DIVERSITY AND FINANCIAL DISTRESS: EVIDENCE FROM NON-FINANCIAL COMPANIES IN INDONESIA - Muthia, Fida; Putri, Melisa; Andaiyani, Sri (Jurnal Riset Bisnis dan Manajemen, 2024)
This research aims to empirically test the influence of board gender diversity on the likelihood of financial distress in non-financial companies in Indonesia. The percentage of women on the board of directors and board of commissioners is used as a proxy for the board gender diversity variable. Financial distress is measured using the Altman Z-score ratio. 2553 total observations were used from 2018-2022 to measure the effect of board gender diversity on the likelihood of distress. The results of logistic regression show that the presence of women on the board of directors and board of commissioners reduces the possibility of financial distress. The research results also show that the increase in supervision is directly proportional to the number of members of the board of directors and board of commissioners. The results of these findings can be input for decision makers regarding regulations on the number of women in company top management.